Analysis of the Implementation of the Love Curriculum Replacing the Independent Curriculum in Madrasah - Chanifudin, Chanifudin; Sa'diah, Halimatu; Nopita, Rini; Suswanto, Suswanto (Research, Training and Philanthropy Institution Natural Aceh, 2025)
The Independent Curriculum, implemented nationally since 2022, is viewed as not fully meeting the needs of Islamic education, which prioritizes the development of students’ spiritual, moral, and practical character. In the Madrasah context, a curriculum model is required that more explicitly integrates values of compassion, empathy, and love for God, fellow human beings, and the environment. Responding to this gap, the Ministry of Religious Affairs of the Republic of Indonesia introduced the Love Curriculum as an alternative and corrective initiative to strengthen the value-based dimensions that are considered lacking in the Independent Curriculum.This article aims to analyze the implementation of the Love Curriculum as a substitute for the Independent Curriculum in Madrasah. A descriptive qualitative method was employed, involving interviews, classroom observations, and document analysis in selected educational institutions that have begun adopting the curriculum. The results indicate that the Love Curriculum effectively revitalizes the humanistic and transformative essence of Islamic education and contributes to the development of students’ noble character, social sensitivity, and spiritual awareness. Nonetheless, its implementation faces several challenges, including teacher readiness, the integration of values into lesson plans, and the monitoring of classroom practice. Therefore, continuous professional development and supportive policies are recommended to ensure the Love Curriculum becomes embedded in the learning culture of Madrasah in a consistent and sustainable manner